2014
DOI: 10.4236/pp.2014.57070
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Magnesium Intake Related to C-Reactive Protein in Newly Diagnosed Coronary Heart Disease Patients at Middle Zone, Gaza Strip. A Hospital Based Study

Abstract: Coronary Heart Disease (CHD) is a highly prevalent disease all over the world. Magnesium (Mg) plays a role in CHD but it is still unclear. C-Reactive Protein (CRP) is an inflammatory marker which may rise in CHD. Aim of study: To assess the impact of dietary Mg intake and its level in relation to CRP among newly diagnosed CHD at middle zone of Gaza Strip. Methodology: Patients (n = 140) with confirmed CHD, 50 ± 10 years, presented in the cardiac care unit at Aqsa Martyr's Hospital between 1 April 2012 and 30 D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 72 publications
2
0
0
Order By: Relevance
“…This agrees with El-Hissi et al [30] who conducted a case control study included 100 subjects and assessed association between serum CRP and risk of CAD, they found a direct statistically significant relationship , in which percent of cases with positive CRP was (32.9%) higher than controls (12.9%).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This agrees with El-Hissi et al [30] who conducted a case control study included 100 subjects and assessed association between serum CRP and risk of CAD, they found a direct statistically significant relationship , in which percent of cases with positive CRP was (32.9%) higher than controls (12.9%).…”
Section: Discussionsupporting
confidence: 79%
“…This accords with many studies [30]- [34], that revealed CAD became common with advancing in age, among men by 45 years, and among women by 55 years.…”
Section: Discussionsupporting
confidence: 78%